2021
DOI: 10.1002/vro2.12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary fish oil supplementation on DNA damage in peripheral blood lymphocytes of nine healthy dogs

Abstract: Background Fish oil (FO) supplementation as a source of omega 3 fatty acids is associated with beneficial effects on health. However, high unsaturated fatty acid content in the diet could result in increased lipid peroxidation and damage to proteins, lipids and DNA. We evaluated the effect of dietary FO supplementation on DNA damage in peripheral blood lymphocytes of dogs. Additionally, we determined the effect of FO supplementation on lipid peroxidation and lipid profile of these dogs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
5
1
Order By: Relevance
“…Our results are also in keeping with findings that fish oil supplementation did not result in genotoxic effects and can actually provide protection from genotoxic effects in in vivo models of rats, dogs and humans [15] , [18] , [20] .…”
Section: Discussionsupporting
confidence: 91%
“…Our results are also in keeping with findings that fish oil supplementation did not result in genotoxic effects and can actually provide protection from genotoxic effects in in vivo models of rats, dogs and humans [15] , [18] , [20] .…”
Section: Discussionsupporting
confidence: 91%
“…Supplementation of a dog’s diet with fish oil rich in omega-3 fatty acids (1 g per day, 90 days) reduced DNA damage as assayed by alkaline single-cell electrophoresis in peripheral blood lymphocytes from five dogs receiving fish oil compared with four dogs receiving a standard diet. The DNA damage index was reduced already at day 30 and became more pronounced at day 90 [ 81 ]. Bioactive oligopeptides (FWKVV and FMPLH) from the protein hydrolysate of the miiuy croaker ( Acanthuriformes , Miichthys miiuy ) muscle protected human umbilical vein endothelial cells (HUVECs) against damage produced by hydrogen peroxide.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…The levels of total FO (or EPA + DHA) offered to dogs as well as the DHA-to-EPA ratio were lower in all of those trials than in the current trial. In the three trials that showed no effect of FO on triglycerides, one tested FO as a supplement in client-owned, mixed-breed dogs with an intake of 0.03–0.04 g FO/kg BW ( 88 ), while the other two studies used FO in food form at 0.11 g EPA+DHA/kg BW in Belgian Shepherd working dogs ( 89 ) and 0.06 g FO/kg BW in beagles ( 36 ). In the two trials that showed a reduction in triglycerides with FO, one tested FO as a supplement in miniature Schnauzers with primary hyperlipidemia (intake of 0.10 g EPA+DHA/kg BW, though it is unclear how this amount was present in one FO capsule) ( 84 ) and the other tested a food form of FO (0.10 g EPA+DHA/kg BW) in beagles ( 66 ).…”
Section: Discussionmentioning
confidence: 99%